Geophysical applications in geomorphology: [ ... most of the papers were originally presented at the "International Workshop Geophysical Techniques in Geomorphology" held in Bonn, Germany in February 2002] - Schrott, Lothar (Zeitschrift für Geomorphologie, 2003)
CD-ROM contains a demo version of the program REFLEXW for the 2- and 3- dimensional processing and interpretation of reflection, refraction and transmission data with a wide range of applications: GPR, reflection seismics, refraction seismics, borehole transmission, ultrasound
CD-ROM u.d.T.: Sandmeier Software : refraction seismics demo REFLEXW, Version 3.0
Keywords: Konferenzschrift; Aufsatzsammlung; Geomorphologie; Prospektion; Geophysik